Aptamer-Targeted Plasmonic Photothermal Therapy of Cancer - Olga S. Kolovskaya; Tatiana N. Zamay; Irina V. Belyanina; Elena Karlova; Irina Garanzha; Aleksandr S. Aleksandrovsky; Andrey Kirichenko; Anna V. Dubynina; Alexey E. Sokolov; Galina S. Zamay; Yury E. Glazyrin; Sergey Zamay; et al. (Molecular Therapy: Nucleic Acids, 2017)
Novel nanoscale bioconjugates combining unique plasmonic photothermal properties of gold nanoparticles (AuNPs) with targeted delivery using cell-specific DNA aptamers have a tremendous potential for medical diagnostics and therapy of many cell-based diseases. In this study, we demonstrate the high anti-cancer activity of aptamer-conjugated, 37-nm spherical gold nanoparticles toward Ehrlich carcinoma in tumor-bearing mice after photothermal treatment. The synthetic anti-tumor aptamers bring the nanoparticles precisely to the desired cells and selectively eliminate cancer cells after the subsequent laser treatment. To prove tumor eradication, we used positron emission tomography (PET) utilizing radioactive glucose and computer tomography, followed by histological analysis of cancer tissue. Three injections of aptamer-conjugated AuNPs and 5 min of laser irradiations are enough to make the tumor undetectable by PET. Histological analysis proves PET results and shows lower damage of healthy tissue in addition to a higher treatment efficiency and selectivity of the gold nanoparticles functionalized with aptamers in comparison to control experiments using free unconjugated nanoparticles.